Keadilan Restoratif Sebagai Upaya Penyelesaian Tindak Pidana Dalam Sistem Hukum di Indonesia - Mochamad Sukedi; I Nengah Nuarta (Jurnal Preferensi Hukum, 2024)
The justice that has been taking place in the criminal justice system in Indonesia is retributive justice, while what is expected is restorative justice, namely a process where all parties involved in a particular criminal act work together to solve the problem, how to deal with the consequences in the future, not yet regulated by strict norms that prevent criminal cases from having to be resolved outside of court using restorative justice. Based on the background above, researchers are very interested in studying: 1) How is the development of restorative justice in the Indonesian legal system? and 2) What are the principles of restorative justice in resolving criminal cases in Indonesia? The type of research used in this research is normative legal research. The development of restorative justice in the Indonesian legal system is based on the lack of satisfaction from the existing criminal justice system process, where it is felt that it does not meet the needs of the community, because in a criminal justice system process the parties in conflict are not involved but only involve between perpetrators and the state. Victims and the community are not involved in conflict resolution, in contrast to the principle of restorative justice where victims and the community are also involved in conflict resolution. The principle of restorative justice in resolving criminal cases in Indonesia is not something relatively new in Indonesia because it is a dispute resolution model which is one type of alternative punishment in the criminal law system in line with the aim of criminal sanctions according to the concept of customary law, namely restoring cosmic balance, balance between The world was born with the supernatural world, to bring a sense of peace between fellow citizens or between members of society and their community.